Jazz. Episode ten, A masterpiece by midnight [videorecording (DVD)] - Burns, Ken, 1953-; David, Keith; Marsalis, Branford; Hancock, Herbie, 1940-; Marsalis, Wynton, 1961- (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
In the 1960s, jazz fragments into the avant-garde and many divided schools of thought. Many jazz musicians like Dexter Gordon are forced to leave America in search of work while other use the music as a form of social protest: Max Roach, Charles Mingus, and Archie Shepp make overtly political musical statements. John Coltrane appeals to a broad audience before his untimely death. Saxophonist Stan Getz helps boost a craze for bossa nova music, but in the early 1970s, jazz founders Louis Armstrong and Duke Ellington pass away. Miles Davis leads a movement of jazz musicians who incorporate elements of rock and soul into their music and "fusion" wins listeners. By the mid-1980's, jazz begins to bounce back led by Wynton Marsalis and a new generation of musicians. Now as it approaches its centennial, jazz is still alive, still changing and still swinging.